Machinability study of high thermal conductivity tool steel (HTSC-150 ) in hot press die - Ahmad Nur Zakwan, Ahmad Nazari (2013)
Nowadays in Hot press die, the die itself has a strong contribution to overall investment and maintenance costs and above all, the influence on produced component cost is unusually high. Incompatible usage of machining parameters may lead to the greater cost investment due to the frequent changing of tool. The optimum machining parameter can help in manufacturing operation by improved and adjusted the manufacturing process and at the same time increase their profit. In order to be a competent player in the market, a better material with higher thermal conductivity can contribute in short cycle time of hot stamping process besides improve the process and product performance. HTCS-150 is highly demand materials for making die with high thermal conductivity properties. It was predicted that this HTCS 150 will be common material in future, so that it is important to improve hot press cycle time. This study basically shows a detailed study to investigate the influence of machining parameters to tool wear rate and surface roughness and provides the optimum machining parameters of HTCS 150 both during annealed and hardened condition. In this study, the recorded data was analysed using Signal/Noise (S/N) ratio to find the significant of control factors level to the response. The optimum level of machining parameter was obtained at lowest mean of control factors as low value of tool flank wear rate and low surface roughness was desired. Further analysis was done to predict the flank tool wear rate and surface roughness through first linear model regression. Generally, the data show the spindle speed was the most dominant control factor contributing to the flank tool wear rate and surface roughness. This proved by the S/N ratio showed at the surface roughness response for annealed HTCS- 150 and both tool flank wear rate and surface roughness for hardened HTCS-150. However, depth of cut was the most contributing factor for tool flank wear rate during machining of annealed HTCS-150.